Professional progress of future teacher of physical culture trends with the use of information technologies in professional preparation. - Dragnev Y.V. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2011)
In the article professional progress of future teacher of physical culture trends are examined with the use of information technologies in professional preparation. It is shown the determination of the concept „tendency". It is marked that modern progress of trade education trends are determined the hard requirements of market to quality of productive labour. By anchorwomen specified scientists that the improvement of the informative providing of educational process and scientific researches of industry of physical culture and sport is impossible without application of innovative facilities of informing, and informatization in the institute of higher of athletic type foresees perfection of forms and methods of organization of educational process.